Lactate infusion increases circulating pro-brain-derived neurotrophic factor levels in humans - Röja, Julia; Ameller, Nicolas Fiori; Grip, Jonathan; Apró, William; Moberg, Marcus (Frontiers in Cellular Neuroscience, 2025)
Brain-derived neurotrophic factor (BDNF) is a key mediator of neuroplasticity and responsive to acute physical exercise, providing a link between exercise and brain health. Lactate, a metabolite related to exercise, has been proposed as a potential mediator of the BDNF exercise response; however, lactate’s role in isolation has not yet been determined. To investigate this, 18 young, healthy volunteers (50% female) were recruited to donate blood and muscle before, during, and after a 1-h venous infusion of sodium lactate (125 μmol × kg FFM–1 × min–1) or isotonic saline. Muscle and blood samples were collected during 120 min of recovery from the infusion. Samples were analyzed for pro-BDNF and mBDNF using enzyme-linked immunosorbent assay and immunoblotting. The participants reached a peak plasma lactate level of 5.9 ± 0.37 mmol × L–1 in the lactate trial (p = 0.0002 vs. Pre). Plasma pro-BDNF levels increased 15 min post lactate infusion and stayed elevated throughout the recovery (55%–68%, p < 0.0286 vs. Saline) while plasma and serum levels of mBDNF showed no significant change (p > 0.05 vs. Saline). Muscle pro-BDNF levels were also unaltered by the lactate infusion (p > 0.05 vs. Saline); however, the expression of pro-BDNF correlated with the proportion of type I muscle fiber area (fCSA%) of the participants (n = 18, r = 0.6746, p = 0.0021). Muscle levels of the mBDNF isoform were non-detectable. In conclusion, these results suggest that lactate in isolation affects circulatory pro-BDNF, but not mBDNF levels. This implies that lactate may partly mediate the exercise response of pro-BDNF in humans.